PEMBUATAN BAHAN AJAR KOMIK SAINS INKUIRI MATERI BENDA UNTUK MENGEMBANGKAN KARAKTER SISWA KELAS IV SD (UPEJ Unnes Physics Education Journal, 2012)
The decrease of Indonesia rank in international and degradation of nation’s morality have changed the educational field. One of the solutions to overcome this deterioration is using learning materials which are able to improve the students’ understanding and to develop their character. The purpose of this research is to arrange learning learning materials which are able to improve the students’ understanding especially in science subject and to develop students’ positive character. The inquiry elements and the nuance of positive characters are applied in the plot of comic. This research cobsists of readability test, proper test and trial test using pre experimental design. The result shows that the degree of readability and feasibility are 80% anda 91,2% which means that the science comic is easily understood and proper to be used as a learning material. The result of gain test shows that there is an improvement in students’ cognitive skill. Based on the feasibility test, science comics could develop students’ character.